The Impact of Household Cooking Fuel Choice on Healthcare Expenditure in Ghana - Azorliade, Dictus Atsu; Twerefou, Daniel Kwabena; Dovie, Delali Benjamin K. (Frontiers in Environmental Science, 2022)
This paper investigates the impact of household cooking fuel choice on household healthcare expenditure as well as the socioeconomic and demographic factors that influence household healthcare expenditure. We employed the Tobit regression technique and data from the sixth and seventh rounds of the Ghana Living Standards Survey conducted in 2012/13 and 2016/17 respectively. The results indicate that in 2012/13, relative to households using wood as cooking fuel, households using charcoal and liquefied petroleum gas are 54.40 and 115.09 percentage points less likely to spend on healthcare services. However, the figure reduced to 28.15 and 103.25 percentage points in 2016/17 attributable possibly to a reduction in biomass energy use resulting from government liquefied petroleum gas promotion programs which helped households transition to the use of cleaner fuels. Age, education, illness reporting of household head, total household expenditure, household size and region of residence were found to be the determinants of household healthcare expenditure. Policy choices should focus on the use of cleaner fuel options including sustaining and extending the rural LPG promotion programme as well as reducing the use of dirty fuels.